Surveillance Programme of IN-patients and Epidemiology (SPINE): implementation of an electronic data collection tool within a large hospital in Malawi. - Miguel A SanJoaquin; Theresa J Allain; Malcolm E Molyneux; Laura Benjamin; Dean B Everett; Oliver Gadabu; Camilla Rothe; Patrick Nguipdop; Moses Chilombe; Lawrence Kazembe; Servace Sakala; Andrew Gonani; et al. (PLoS Medicine)
Miguel Sanjoaquin and colleagues describe their experience of setting up an electronic patient records system in a large referral hospital in Blantyre, Malawi.